The law and economics of child support payments - Comanor, William S. (Cheltenham : Northampton, MA : Edward Elgar, 2004)
To understand the issues involved, leading lawyers and economists examine various facets of the child support system from a law and economics perspective. They consider the incentives faced by both custodial and non-custodial parents, and search for policy actions that are more incentive-compatible for all participants. The assumptions underlying current child support guidelines are discussed, as are the ways in which child support payments affect family structure, teenage delinquency and income disparities between parents.
Includes bibliographical references and index.
oif 11/02/15, ijb 20/02/2019
Loan
Keywords: Child support; Child welfare; Law and economics